Fünfzig Jahre Sammlung van der Grinten 1946-1996 : Stiftung Museum Schloss Moyland - Sammlung van der Grinten - Joseph Beuys Archiv des Landes Nordrhein-Westfalen. - Museum Schloss Moyland, Bedburg-Hau; Acht, René; Beyerle, Burkhart; Brüx, Walther; Burgeff, Hans Karl; Creij, Reggy Havekes-van; Damsté, Christiaan Paul; Dorren, Maurice; Ernsting, Bernd; Gottlob, Richard; Gutmann, Franz; Haug, Ute; et al. (Bedburg-Hau : Museum Schloss Moyland Bedburg-Hau, 1999)
Acht, René Charles ; Albers, Josef ; Andrae, Elisabeth ; Andriessen, Cees ; Bachmayer, Horst ; Barth, Ruodi ; Bernhard, Franz ; Betts, Heather ; Beuys, Joseph ; Beyerle, Burkhart ; Blumenthal, Hermann ; Bohrmann, Karl ; Bollschweiler, Jacob Friedrich ; Brodwolf, Jürgen ; Brüx, Walther ; Burgeff, Karl ; de Caranza, Amédée Duc ; Coester, Otto ; Crummenauer, Rolf ; Damsté, Christiaan Paul ; Denis, Maurice ; Dix, Otto ; Dorazio, Piero ; Dreher, Peter ; Drove, Winfried ; Durousseau, Paul Léonard ; Eckmann, Otto ; Eerdmans, Emmy ; Eggenschwiler, Franz ; Englaender, Alfred ; Ernsting, Bernd ; Falken, Herbert ; Fassbender, Joseph ; Feininger, Lyonel ; Fiedler, Otto Herbert ; Flora, Paul ; Frenken, Jacques ; Frenken, Ton ; Friedlaender, Johnny ; Getlinger, Fritz ; Gijsen, Jo ; Gottlob, Richard ; Goya, Francesco ; van der Grinten, Franz Joseph ; van der Grinten, Hans ; Grochowiak, Thomas ; Gutmann, Franz ; Hackemann, Kai ; Haden, Sir Francis Seymour ; Hallensleben, Georg ; Heck, Johann Peter ; Heckel, Erich ; Heerich, Erwin ; Heindrichs, Heinz-Albert ; Heinsheimer, Fritz ; Hendriks, Berend ; Hillebrand, Elmar ; Hockney, David ; Hötzendorff, Theodor von ; Hülster, Hans ; Hüppi, Alfonso ; Huszát, Vilmos ; Jansen, Gerd ; Jochimsen, Margarethe ; John, Erich Wilhelm ; Joswich-Rodatz, Clara ; Kadow, Gerhard ; Kalinowski, Horst Egon ; Kamps, Heinrich ; Keining, Horst ; Klinger, Max ; Knaupp, Werner ; Koepplin, Dieter ; Kollwitz, Kathe ; Köpcke, Arthur ; Kopfermann, Sigrid ; Kühnapfel, Maria ; Lablais, Michel ; Lagae, Jules ; Lahms, Dieter ; Lamers, Hanns ; Lechtenberg, Adolf ; Lechter, Melchier ; Liebermann, Max ; de Locht, Peter H. van ; Loeber, Louise Maria (Lou) ; Loth, Wilhelm ; Marcks, Gerhard ; Martens, Karel ; Märtens, Klaus ; Mataré, Ewald ; etc.
biografie
Fünfzig Jahre Sammlung Van Der Grinten : 1946-1996, Museum Schloss Moyland, Bedburg-Hau, 20. März - 5. September 1999
Duits
boek